1996
DOI: 10.1002/chin.199630321
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 1,2‐Amino Alcohols and Their Heterocyclic Derivatives as Chiral Auxiliaries in Asymmetric Synthesis

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 1 publication
0
47
0
Order By: Relevance
“…In this example, quinine was used as the resolving agent [8,9]. 12 [10,11] and Evans [12][13][14] auxiliary methods, and there are many examples in the literature that there is a high probability of success with an analogous system [13]. The methodology is excellent for smaller-scale applications.…”
Section: Resolution Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this example, quinine was used as the resolving agent [8,9]. 12 [10,11] and Evans [12][13][14] auxiliary methods, and there are many examples in the literature that there is a high probability of success with an analogous system [13]. The methodology is excellent for smaller-scale applications.…”
Section: Resolution Approachesmentioning
confidence: 99%
“…Phenylglycinol (14) itself can be used as a chiral template transferring the nitrogen in an asymmetric Strecker reaction (Scheme 12.16). However, in some examples of this approach, caution must be exercised as epimerization has been observed during hydrolysis of the nitrile group [60][61][62][63].…”
Section: Strecker Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The set up of a methodology for chiral auxiliary mediated asymmetric carbon-carbon bond formation may be an interesting goal in organic synthesis [1][2][3]. Chiral oxazolidin-2-ones have been frequently utilized as chiral auxiliaries (Evans' chiral auxiliaries) [4,5] in asymmetric synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Chiral 2-oxazolidinones, first reported by Evans in 1981, 5 have proven to be highly versatile chiral auxiliaries, with high asymmetric induction achieved in alkylations, aminations, azidations, brominations, hydroxylations, aldol additions, DielsAlder cycloadditions and conjugate reactions. [6][7][8][9] Therefore, we wished to extend this chlorination chemistry to α-thiopropanoyloxazolidin-2-ones, and explore the asymmetric induction in reactions of the resulting α-thio-β-chloropropenyloxazolidin-2-ones, focussing specifically on diastereoselective oxidation (Scheme 1). We have recently shown that with simple chiral amide auxiliaries, some, albeit modest, diastereocontrol is possible.…”
Section: Introductionmentioning
confidence: 99%